Teacher Commitment and Learning Quality : Encouraging Teaching Factory at Bekasi Islamic Private Vocational School - Rustomo Rustomo; Imam Makruf; Raden Lukman Fahroni; Giyoto Giyoto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
The aim of this research is to analyze the description of educators' dedication to the quality of education through use of teaching factories as a way to close the competency gap required by the industrial sector to study at private Islamic vocational schools in Bekasi Regency. The research method used a qualitative descriptive with three-stream analysis of data reduction, data presentation and drawing conclusions from the results of observations and in-depth interviews with participants including school principals and teachers as heads of the teaching factory program and the Bekasi District Education Office as supervisors of the implementation of the teaching factory program. A tree diagram used to explain the structured flow of the results of observations and in-depth interviews. The findings showed that the dedication of teaching staff at the Bekasi Regency Islamic Private Vocational School in achieving the learning quality of the teaching factory program was still very low. Where it is necessary to encourage school principals and related agencies to be able to innovate learning facilities that are relevant to the industrial world at the same level. Encouragement of compensation and opportunities at the next level of education. Efforts to encourage the teaching factory program to emphasize the importance of learning facilities in schools as a means of industrial practice in the classroom. Other efforts include the rights and obligations in building teacher dedication to achieve competent.